Ventilation record of cold-water corals from Mauritania over the last 30.000 years - Beisel, Elvira; Frank, Norbert; Wienberg, Claudia; Friedrich, Ronny (PANGAEA, 2025)
Combined 230ThU and 14C ages in cold-water corals allow accurate reconstruction of ventilation in the past. Here we present a ventilation record of cold-water corals from Mauritania (GeoB 14904-2, 517m water depth) over the last 30,000 years. The core was retrieved with a gravity corer during the RV Maria S. Merian expedition MSM16-3 Phaeton (Westphal et al 2014) and coral fragments of the species Desmophyllum pertusum (formerly known as Lophelia pertusa) were collected at various core depths. They complement recent findings on the ventilation of the eastern Atlantic (Beisel et al 2023). The corals were precisely dated using 230ThU and 14C dating. The 230ThU method is described in detail in Wefing et al 2017, Kerber et al 2023, the 14C method in Beisel et al (submitted). Benthic-atmosphere ages were calculated with IntCal20 (Reimer et al 2020). Results are discussed in Beisel et al (submitted).
Keywords: 14C dating; 230Th/U dating; Cold-water coral; Mauritania; ventilation